Dietary quality in a sample of adults with type 2 diabetes mellitus in Ireland; a cross-sectional case control study - EGANA, MIKEL (My University, 2013)
BACKGROUND: A number of dietary quality indices (DQIs) have been developed to assess the quality of dietary intake. Analysis of the intake of individual nutrients does not reflect the complexity of dietary behaviours and their association with health and disease. The aim of this study was to determine the dietary quality of individuals with type 2 diabetes mellitus (T2DM) using a variety of validated DQIs. METHODS: In this cross-sectional analysis of 111 Caucasian adults, 65 cases with T2DM were recruited from the Diabetes Day Care Services of St. Columcille's and St. Vincent's Hospitals, Dublin, Ireland. Forty-six controls did not have T2DM and were recruited from the general population. Data from 3-day estimated diet diaries were used to calculate 4 DQIs. RESULTS: Participants with T2DM had a significantly lower score for consumption of a Mediterranean dietary pattern compared to the control group, measured using the Mediterranean Diet Score (Range 0-9) and the Alternate Mediterranean Diet Score (Range 0-9) (mean ± SD) (3.4 ± 1.3 vs 4.8 ± 1.8, P < 0.001 and 3.3 ± 1.5 vs 4.2 ± 1.8, P = 0.02 respectively). Participants with T2DM also had lower dietary quality than the control population as assessed by the Healthy Diet Indicator (Range 0-9) (T2DM; 2.6 ± 2.3, control; 3.3 ± 1.1, P = 0.001). No differences between the two groups were found when dietary quality was assessed using the Alternate Healthy Eating Index. Micronutrient intake was assessed using the Micronutrient Adequacy Score (Range 0-8) and participants with T2DM had a significantly lower score than the control group (T2DM; 1.6 ± 1.4, control; 2.3 ± 1.4, P = 0.009). When individual nutrient intakes were assessed, no significant differences were observed in macronutrient intake. CONCLUSION: Overall, these findings demonstrate that T2DM was associated with a lower score when dietary quality was assessed using a number of validated indices.
PUBLISHED
Keywords: Psychology; Ageing; Immunology, Inflammation & Infection